Along the Rivers and into the Plain: Early Crop Diversity in the Central and Western Balkans and Its Relationship with Environmental and Cultural Variables - Anne de Vareilles; Dragana Filipović; Djurdja Obradović; Marc Vander Linden (Quaternary, 2022)
Agriculture is a complex and dynamic socio-ecological system shaped by environmental, economic, and social factors. The crop resource pool is its key component and one that best reflects environmental limitations and socio-economic concerns of the farmers. This pertains in particular to small-scale subsistence production, as was practised by Neolithic farmers. We investigated if and how the environment and cultural complexes shaped the spectrum and diversity of crops cultivated by Neolithic farmers in the central-western Balkans and on the Hungarian Plain. We did so by exploring patterns in crop diversity between biogeographical regions and cultural complexes using multivariate statistical analyses. We also examined the spectrum of wild-gathered plant resources in the same way. We found that the number of species in Neolithic plant assemblages is correlated with sampling intensity (the number and volume of samples), but that this applies to all archaeological cultures. Late Neolithic communities of the central and western Balkans exploited a large pool of plant resources, whose spectrum was somewhat different between archaeological cultures. By comparison, the earliest Neolithic tradition in the region, the Starčevo-Körös-Criş phenomenon, seems to have used a comparatively narrower range of crops and wild plants, as did the Linearbandkeramik culture on the Hungarian Plain.